2012
DOI: 10.1097/pec.0b013e3182442c0a
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Enema Versus Polyethylene Glycol 3350 for Fecal Disimpaction in Children Presenting to an Emergency Department

Abstract: This pilot study suggests that disimpaction by enema may be superior to PEG for immediate relief of symptoms. Larger trials are needed to assess any advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 0 publications
0
44
0
2
Order By: Relevance
“…Although the authors found no association between clinical response, as reported 4 to 6 weeks later, and ED treatment (7), a subsequent trial involving 79 children concluded that enema disimpaction provides superior, immediate symptom relief compared with PEG (5). In addition to causing children to become ''upset'' (5), sodium phosphate enemas have the potential to result in electrolyte abnormalities (eg, hyperphosphatemia, hypocalcemia, hypernatremia, hypokalemia, metabolic acidosis) (8). In addition to causing children to become ''upset'' (5), sodium phosphate enemas have the potential to result in electrolyte abnormalities (eg, hyperphosphatemia, hypocalcemia, hypernatremia, hypokalemia, metabolic acidosis) (8).…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Although the authors found no association between clinical response, as reported 4 to 6 weeks later, and ED treatment (7), a subsequent trial involving 79 children concluded that enema disimpaction provides superior, immediate symptom relief compared with PEG (5). In addition to causing children to become ''upset'' (5), sodium phosphate enemas have the potential to result in electrolyte abnormalities (eg, hyperphosphatemia, hypocalcemia, hypernatremia, hypokalemia, metabolic acidosis) (8). In addition to causing children to become ''upset'' (5), sodium phosphate enemas have the potential to result in electrolyte abnormalities (eg, hyperphosphatemia, hypocalcemia, hypernatremia, hypokalemia, metabolic acidosis) (8).…”
mentioning
confidence: 90%
“…It has been shown to improve in >50% of children in the ED following enema administration (6,7). Other measures such as symptomatic relief following enema administration were not selected because of potential placebo effect bias and the fact that early improvements in children with constipation do not necessarily translate into long-term benefits (5). Other measures such as symptomatic relief following enema administration were not selected because of potential placebo effect bias and the fact that early improvements in children with constipation do not necessarily translate into long-term benefits (5).…”
Section: Independent Predictors Of Ed Revisits For Ongoing Symptoms Omentioning
confidence: 99%
See 2 more Smart Citations
“…5-7 This may result in a diagnostic and therapeutic approach toward suspected constipation that varies from than algorithms used in the standard outpatient setting. Children undergoing disimpaction in the acute setting are more likely to experience pain relief in comparison to less aggressive therapies, and thus disimpaction per rectum is often employed.…”
Section: Introductionmentioning
confidence: 99%